Continuous Proteolysis of Casein by the Cell Bound Protease of Carum copticum - Rafiq Khan, Mohammad; Muhammad Imran, Raja; Bokhari, Hamim (Asian Journal of Chemistry, 2010)
In this paper, a continuous proteolytic system to prepare protein hydrolysis products for different biological applications is developed. Continuous proteolysis of casein substrate prepared in phosphate buffer (pH 7) by the seeds of Carum copticum packed in a column was attempted. Assuming that the seeds contained a mixture of soluble and cell-bound proteases, the soluble protease was eluted by passing buffer (pH 7) through the packed seeds. The buffered substrate was subsequently run into the column to constitute the system of continuous proteolysis. The products of proteolysis collected in the form of 5 mL fractions were assayed by Lowry's method. The system operated successfully for proteolysis on continuous basis. The extent of proteolysis was significantly high, which went on increasing with the passage of time. The activity of the system did not vanish within the time span of the experiment carried here. The data indicated that the life of cell bound protease of Carum copticum is very long.